Pd-modified CuO–ZnO–ZrO2 catalysts for CH3OH synthesis from CO2 hydrogenation. (12th July 2022) - Ding, Ziluo; Xu, Yamei; Yang, Qiuchen; Hou, Ruijun
Abstract: The Pd-modified Cu–ZnO–ZrO2 quaternary catalysts for CO2 hydrogenation to CH3 OH was investigated. The effect of Pd on CZZ were characterized systematically to illustrate the interaction between Pd and CZZ. The addition of Pd results in an increase in the crystalline sizes of Cu and a higher reduction temperature of bulk CuO. A suitable amount of Pd addition is crucial for the modification of surface Cu sites. 1.0Pd-CZZ shows the highest selectivity for CH3 OH and 0.5Pd-CZZ exhibits the highest intrinsic CH3 OH STY. Excess amount of Pd loadings (1.0% and 1.4%) would result in surface Cu aggregation, and exhibit decreased intrinsic CH3 OH STY. By correlating the characterization and the catalytic performance results, it is inferred that both the independent Cu site and the Cu site with strong interactions are responsible for CH3 OH production. This work would provide molecular insight into the modification of intrinsic surface sites for CH3 OH synthesis from CO2 . Graphical abstract: Image 1 Highlights: A suitable amount of Pd addition is crucial for the modification of surface Cu sites. Both the independent Cu site and the Cu site with strong interactions are responsible for CH3 OH production. H2 spillover between Pd and Cu enhances CH3 OH selectivity over 1.0Pd-CZZ. 0.5Pd-CZZ shows the highest intrinsic CH3 OH STY due to the geometric effect.